Harnessing marine algal polysaccharides for combination cancer therapy: pharmacological mechanisms and clinical perspectives - Zhong, Jing; Chung, Sookja Kim; Han, Xiaoling; Huang, Riming; Xu, Baojun; Wong, Io Nam (Frontiers in Pharmacology, 2025)
Algal polysaccharides (APs) have attracted increasing interest in recent years as adjunctive agents in cancer therapy due to their abundance, low toxicity, and diverse bioactivity. This review explores the pharmacological effects and mechanisms of APs in combination with chemotherapy, radiotherapy, and immunotherapy, as well as their potential as a nano medicine delivery system. It highlights a wide range of biological activities exhibited by APs in combination therapy, including enhanced tumor cell killing, modulation of the tumor immune microenvironment, and protection of healthy tissues from treatment-related toxicity. Furthermore, the review summarizes the advancements in the pharmacodynamics, pharmacokinetics, and safety profiles of APs, emphasizing the need for standardized raw materials, combined strengths analysis, and clinical validation as key future directions.